PROBLEMS FOR THE ACCOUNTING OF POLITICAL PARTIES IN KNOWLEDGE SOCIETY - AURELIAN VIRGIL BALUTA (Challenges of the Knowledge Society)
The society needs good reports from the accounting of political parties. The public power, including the Government, depends on the kind of financing of political parties. The improvement of the control of resources used by the parties accounting is very important. The paper presents the tools for the accounting of political parties in knowledge society. The paper contains the author's opinion on current issues of political party accounting. Arguments are presented against some recent proposals to amend the regulations, arguments in favor of concrete solutions and the analysis of the correlation between accounting expertise and the political parties accounting in the knowledge society.